A review of multistage solar driven photovoltaic–thermal​ components with cascade energy storage system for tri-generation. (November 2022) - Ndwali, Patrick K.; Kusakana, Kanzumba; Numbi, P.B.; Liu, Shuli; Sun, Wei; Cai, Jingyong
Abstract: Energy demand has exponentially increased in recent times, mainly because of population and economic growth as well as high standards of living in commercial and residential buildings. Conventional power systems have been undergoing great transformation owing to the integration of renewable energy sources (RESs) and demand side management programs. Solar Photovoltaic–Thermal (PV/T) is one of the most growing Renewable Energy Resources (RERs) because of its low carbon emission, high energy efficiency, cost effectiveness, readily available, among other benefits. Several researches have been explored to enhance the performance of different components in the building integrated systems distributed solar energy for tri-generation: heating, cooling and electricity generation. The Photovoltaic–Thermal (PV/T) energy system may be enhanced using various advanced control schemes and cooling technologies. Energy storage systems have shown outstanding benefits by improving the reliability and security of modern power systems. Ice Thermal Energy Storage (ITES) systems have been used for cooling loads, while Heat Storage Water Tank (HSWT) are used for hot water demand. Alternatively, battery banks have been used for storing chemical energy and releasing electricity to the demand side. This reviewed work highlights various components of a solar driven grid-connected PV/T energy system, considering the ITES, HSWT and a battery bank under-price based Demand Response (DR) in terms of the optimal sizing and operational control.